Race/Ethnicity Moderates the Association Between Psychosocial Resilience and Movement‐Evoked Pain in Knee Osteoarthritis. Issue 1 (15th March 2019) - Bartley, Emily J.; Hossain, Nadia I.; Gravlee, Clarence C.; Sibille, Kimberly T.; Terry, Ellen L.; Vaughn, Ivana A.; Cardoso, Josue S.; Booker, Staja Q.; Glover, Toni L.; Goodin, Burel R.; Sotolongo, Adriana; Thompson, Kathryn A.; et al.
Abstract : Objective: Racial/ethnic disparities in pain are well‐recognized, with non‐Hispanic blacks (NHBs) experiencing greater pain severity and pain‐related disability than non‐Hispanic whites (NHWs). Although numerous risk factors are posited as contributors to these disparities, there is limited research addressing how resilience differentially influences pain and functioning across race/ethnicity. Therefore, this study examined associations between measures of psychosocial resilience, clinical pain, and functional performance among adults with knee osteoarthritis (OA), and assessed the moderating role of race/ethnicity on these relationships. Methods: In a secondary analysis of the Understanding Pain and Limitations in Osteoarthritic Disease (UPLOAD‐2) study, 201 individuals with knee OA (NHB = 105, NHW = 96) completed measures of resilience (ie, trait resilience, optimism, positive well‐being, social support, positive affect) and clinical pain, as well as a performance‐based measure assessing lower‐extremity function and movement‐evoked pain. Results: Bivariate analyses showed that higher levels of psychosocial resilience were associated with lower clinical pain and disability and more optimal physical functioning. NHBs reported greater pain and disability, poorer lower‐extremity function, and higher movement‐evoked pain compared with NHWs; however, measures of psychosocial resilience were similar across race/ethnicity. In moderation analyses, higher optimism and positive well‐being were protective against movement‐evoked pain in NHBs, whereas higher levels of positive affect were associated with greater movement‐evoked pain in NHWs. Conclusion: Our findings underscore the importance of psychosocial resilience on OA‐related pain and function and highlight the influence of race/ethnicity on the resilience‐pain relationship. Treatments aimed at targeting resilience may help mitigate racial/ethnic disparities in pain.